Produção da cultura da beterraba irrigada com água salina., - Silva, Alexsandro Oliveira da [UNESP]; Klar, Antonio Evaldo [UNESP]; Silva, Enio Farias de França e (My University, 2013)
The use of low quality water for agriculture should be performed with care to avoiding excessive accumulation of salts in the soil so not to harm crop development. In order to evaluate the performance of beets under the infl uence of low water quality, an experiment was conducted in a greenhouse of the Department of Agricultural Engineering, Universidade Estadual Paulista in Botucatu, Brazil, from April to July 2012. We used the beet (Beta vulgaris L.) in a completely randomized design with 6 treatments and 5 replications, totaling 30 plots. Treatments consisted of NaCl solutions at different concentrations (2.0, 3.0, 4.0, 5.0 and 6.0 dS m-1) plus a control treatment corresponding to water with no additional salt and electrical conductivity of roughly 0.26 dS m-1. Variables evaluated were total production, commercial production, plant height, number of plants and root diameter. Production of the beet crop was affected by the increasing salinity of irrigation water, characterized by reduced root production of the beets. Total and commercial production showed reductions of 8.82 and 12.2% in accordance with the unit increase of salinity.

A utilização de água de qualidade inferior para a agricultura deve ser realizada com devido cuidado evitando-se o acúmulo excessivo de sais no solo para não prejudicar o desenvolvimento das culturas. Com o objetivo de avaliar o desempenho da cultura da beterraba sob o efeito de águas de qualidade inferior, realizou-se um experimento em casa de vegetação do Departamento de Engenharia Rural da Universidade Estadual Paulista, Botucatu, SP, no período de abril a julho de 2012. Utilizou-se a cultura da beterraba (Beta vulgaris L.) em delineamento experimental inteiramente casualizado, com 6 tratamentos e 5 repetições, totalizando 30 parcelas. Os tratamentos consistiram de soluções de NaCl de diferentes condutividades elétricas (2,0; 3,0; 4,0; 5,0 e 6,0 dS m-1) além de um tratamento testemunha correspondente a água sem adição de sal com condutividade elétrica em torno de 0,26 dS m-1. Avaliaram-se as variáveis, produção total, produção comercial, altura das plantas, número de plantas e diâmetro da raiz. A produção da cultura foi prejudicada pelo aumento da salinidade da água de irrigação, caracterizando redução na produção das raízes da cultura. A produção total e comercial apresentaram uma de redução de 8,82 e 12,2% de acordo com o aumento unitário da salinidade do solo.
Beet production with salt water irrigation
Keywords: Beta vulgaris L.; Electrical conductivity; Evapotranspiration; Beta vulgaris L.; Condutividade elétrica; Evapotranspiração